From Budgets To Video News Releases: Television News Components In Agricultural Communications Programs At Land·Grant Universities - James Booth; Ricky W. Telg; Edward J. Smith; Don E. Tomlinson (Journal of Applied Communications, 1992)
The 133-item questionnaire was designed to learn, first, whether a given agricultural communications department had a television news component (TNC): and for those that did the resource commitment to each of them, the types and natures of the projects produced, how audiences were defined, and answers relating to production, distribution, marketing, equipment and demographics.